Preschool teachers’ perspectives on (haptic) technology in the classroom - Pila, Sarah; Lauricella, Alexis R.; Piper, Anne Marie; Wartella, Ellen (Frontiers in Education, 2022)
One particularly exciting platform with the potential to teach science, technology, engineering, and math (STEM) in early childhood classrooms is the tablet. However, one challenge in using these devices for STEM learning is that traditional tablets lack important sensory information. The emerging technology of haptic (or tactile) feedback touch-screen displays might reduce this barrier. In order to better understand pre-school teachers’ attitudes toward haptic feedback technology for teaching STEM concepts, we conducted three focus groups. From the focus group data, researchers identified themes around current classroom practices with technology for STEM learning, teachers’ reactions to the haptic feedback tablet, and their impression of the implications of its use in early childhood education. These themes provide insight on teachers’ attitudes and could influence the design of future STEM apps created for haptic feedback tablets.